Flow cytometric analysis of hepatopancreatic cells from Armadillidium vulgare highlights terrestrial isopods as efficient environmental bioindicators in ex vivo settings - Panza, Giovanna; Montanari, Mariele; Lopez, Daniele; Burattini, Sabrina; Ciacci, Caterina; Fumelli, Piermarco Paci; Pasini, Giovanni; Fusi, Vieri; Giorgi, Luca; Grandoni, Francesco; Papa, Stefano; Santolini, Riccardo; et al. (Environmental science and pollution research international, 2024)
Several studies have reported the high bioindication capacity of Isopoda (Crustacea, Oniscidea), which is related to their important ability to accumulate contaminants, usefulness in soil ecotoxicology and bioindication activities. Any change in the isopod population, diversity and life cycle can indicate relevant pollution levels. The analysis of target tissues, such as the hepatopancreas, is another emerging approach (from a cytologic/histological level) to detect contaminant accumulation from different sources. In this study, tissue disaggregation procedures were optimised in the hepatopancreas, and flow cytometry (FC) was applied to detect cell viability and several cell functions. After disaggregation, two hepatopancreatic cell types, small (S) and big (B), were still recognisable: they differed in morphology and behaviour. The analyses were conducted for the first time on isopods from sites under different conditions of ecological disturbance through cytometric re-interpretation of ecological-environmental parameters. Significant differences in cell functional parameters were found, highlighting that isopod hepatopancreatic cells can be efficiently analysed by FC and represent standardisable, early biological indicators, tracing environmental-induced stress through cytologic/histologic analyses.